(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: During the formation of the limbs, a simultaneous production of androgens occurs. It has also been noticed that when genetic process is inhibited, it can lead to complications affecting the limbs. It is therefore believed that testosterone influences the development of the limbs. Aim: This study therefore looked at the association between second toe length and androgen linked behaviours. Materials and Method: Three hundred (166 males and 134 females) subjects who were students of Basic Medical Sciences, Delta State University, Abraka aged 18 and above, were selected using the cross-sectional descriptive study design. Second toe length was observed, standardize questionnaire on handedness, competition and aggregation was administered to students. Data obtained were analyzed with Statistical Package for Social Sciences. Results: This study established a significant association between 2nd toe length and some androgen linked behaviours. Significant association between subjects with longer 2nd toe and competitiveness was observed (p<0.05) as well as aggressive behavior. Conclusion: From this study, it was deduced that androgens influence 2nd toe length and 2nd toe length also influences androgen linked behaviours such as competition and aggression. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.779-789